Antimicrobial potential of the leaves of Citrus grandis (L.) Osbeck collected from Iraq: Bioassay-guided isolation of sinensetin as the anti-MRSA compound - Al-Majmaie, Shaymaa; Nahar, Lutfun; Rahman, M Mukhlesur; Sharples, George P; Sarker, Satyajit D (Fitoterapia, 2025)
Infections caused by antibiotic-drug-resistant microorganisms are a major global health concern, and they result in millions of deaths every year. Methicillin-resistant Staphylococcus aureus (MRSA) is one of such drug-resistant microbial strains, and new and effective antimicrobial agents are desperately needed to combat infections caused by MRSA. In the search for effective anti-MRSA agents, the leaves of Citrus grandis (Rutaceae), also known as C. maxima, were investigated. Implementing a bioassay-guided approach, sinensetin (2), which is a polymethoxyflavone, was isolated as a promising anti-MRSA compound, showing inhibitory activity against three (EMRSA-15, MRSA340802 and MRSA274819; MIC values 128-256 μg/mL) of five MRSA strains tested in the present study. Five other flavonoids 6,7,8,3',4'-pentamethoxyflavone (1), cirsilineol (3), nobiletin (4), 5-desmethylsinensetin (5) and hesperidin (6) were isolated from the dichloromethane extract of this plant. They displayed varied levels of antimicrobial activities against the tested microbial strains, Micrococcus luteus NCTC 7508, Escherichia coli NCTC 12241 and Pseudomonas aeruginosa NCTC 12903, and a fungal strain, Candida albicans ATCC 90028, but not against Staphylococcus aureus NCTC 12981. Sinensetin (2) also exhibited strong antimicrobial activity against the fungal strain C. albicans with an MIC value of 0.0625 mg/mL. The chemical structures of all isolated compounds were unequivocally elucidated by spectroscopic means (1D and 2D NMR and HR-ESIMS). The present study revealed sinensetin (2) as a potential structural template for generating structural analogues and developing anti-MRSA agents and provided scientific evidence supporting the traditional uses of C. grandis in the treatment of microbial infections.
Keywords: Plant Leaves; molekulární struktura; Methicillin-Resistant Staphylococcus aureus; Plant Extracts; flavonoidy; Phytochemicals; antibakteriální látky; Microbial Sensitivity Tests; Anti-Bacterial Agents; Flavonoids; mikrobiální testy citlivosti; listy rostlin; rostlinné extrakty; Candida albicans; Molecular Structure; fytonutrienty; methicilin rezistentní Staphylococcus aureus; Citrus